A study of the effect of multimodal input on vocabulary acquisition: Evidence from online Chinese language learners - Binyu Xing;Haiwei Zhang (Language Teaching Research, 2025)
In response to the growing prevalence of online second language learning and the burgeoning field of international Chinese language education, this study examines the impact of multimodal inputs (MMI) on vocabulary acquisition within online environments among learners of Chinese as a second language (CSL). A teaching intervention was conducted with 90 Mongolian CSL learners, who were grouped into audiovisual, audio, and visual groups. The findings indicate that the audiovisual condition significantly improved vocabulary retention compared to the single-modality conditions in a delayed post-test. Nevertheless, the efficacy of the MMI treatment was observed to vary with learners’ proficiency levels, with beginner-level CSL learners deriving greater benefit from MMI than intermediate-level learners. Furthermore, participants expressed both favorable and critical perspectives regarding the application of MMI in vocabulary instruction. These results highlight the potential of MMI interventions to enhance vocabulary learning in online second-language education, while also underscoring the necessity of considering learners’ target language proficiency and their attitudes when developing MMI-based instructional approaches.